On M-projectively flat LP-Sasakian manifolds - Zengin, F.Ö. (Український математичний журнал, 2013)
In the present paper, we study the nature of LP-Sasakian manifolds admitting the M-projective curvature tensor. It is examined whether this manifold satisfies the condition W(X, Y ).R = 0. Moreover, it is proved that, in the M-projectively flat LP-Sasakian manifolds, the conditions R(X, Y ).R = 0 and R(X, Y ).S = 0 are satisfied. In the last part of the paper, an M-projectively flat space-time is introduced, and some properties of this space are obtained. Вивчається природа многовидів Сасакяна, що допускають M-проективний тензор кривизни. Перевірено, чи задовольняє цей многовид умову W(X, Y ).R = 0. Більш того, доведено, що умови R(X, Y ).R = 0 та R(X, Y ).S = 0 виконуються для M-проективно плоских LP-многовидів Сасакяна. В останній частині роботи введено M-проективно плоский простір-час та встановлено деякі властивості цього простору.